Efforts to Prevent the Crime of Motor Vehicle Theft through Optimizing Dialogic Patrol - Anfasa Omar Ibra (Indonesian Journal of Police Studies, 2021)
Dialogical patrols as a preventive effort should be able to reduce the number of motored vehicle theft criminal cases. However, in reality, cases of motor vehicle theft in South Tangerang City are still high. In this thesis, the author tries to analyze the implementation of dialogical patrols and the factors that influence the implementation of dialogical patrols based on George R. Terry's management theory and AIDDA communication theory. The purpose of this research is to describe the implementation of the dialogical patrols carried out by the Sabhara Unit of the South Tangerang Police and to analyze the factors that influence the implementation of the dialogical patrols themselves. This study used a qualitative approach with interviews to dig deeper into the facts. Resource persons in this study were selected based on their positions and functions. Data analysis in this study used data reduction, data presentation and final conclusions in qualitative research. The findings of the study indicate that motor vehicle theft crimes are still common in South Tangerang City. So the South Tangerang Police Sabhara Unit conducts dialogical patrols to prevent and reduce the occurrence of motor vehicle theft crimes. Apart from officers, community participation is also very much needed so that prevention of motor vehicle theft can be optimal. There are still obstacles in the implementation of dialogical patrols by the Sabhara Unit of the South Tangerang Police, including the lack of quality and quantity of members of the Sabhara patrols so that the messages of social security cannot be conveyed properly to the people of South Tangerang City. There are still obstacles in the implementation of dialogist patrols by the South Tangerang Police Sabhara Unit, among others, the lack of quality and quantity of Sabhara patrol members so that kamtibmas messages have not been conveyed well to the people of South Tangerang City. Keywords: Dialogical patrol, prevention, motored vehicle theft.